INTENTION TO USE MOBILE BANKING APPLICATION: GENDER-BASED - Ignatius Hari Santoso; Lutfi Nurcholis; Erawati Kartika (Jurnal Penelitian Ekonomi dan Bisnis, 2020)
This research is aimed to examine the gender difference toward intention to use the mobile banking application in Semarang. Data is collected by self -  administered questionnaire, and pass over to bank customer which done their financial transaction by Automatic Teller Machine. The Sample used in this research is 50 respondents, consist of 30 male respondents and 20 female respondents who never have a mobile banking application before. The results of this study indicate that there is a gender difference in the intention to use mobile banking applications. On the other side, even it is easy to be used, female customers are not feeling the benefit offered, thus resistant to use mobile banking applications. This result brings another contradiction toward The Technological Acceptance Model. Data is examined by the SPSS application, and Mann – Whitney statistical model.Keywords: Mobile application; bank; gender difference